PERANAN KABUPATEN WAY KANAN DALAM PEMBENTUKAN PRODUK DOMESTIK REGIONAL BRUTO PROPINSI LAMPUNG TAHUN 1999—2002 - Agus Tri Basuki (Jurnal Ekonomi & Studi Pembangunan, 2005)
The objective of this paper is to observe the role of economic development of the Way Kanan District (Kabupaten) in developing the Province of Lampung. The paper concludes that the contribution of the Kabupaten gross regional domestic product (GRDP) of Way Kanan to tile Lampung Provincial GRDP in average was about 0.87 while the average rate of growth of the Kabupaten GRDP was 2.1. In addition, the Way Kanan Kabupaten GRDP contribution was approximately 3.39% of the total provincial GRDP. The Way Kanan is the youngest district in the province; therefore it is reasonable that Kabupaten GRDP has not yet significantly contributed to the Lampung Provincial GRDP